Comparative effectiveness of tocilizumab versus TNF inhibitors as monotherapy or in combination with conventional synthetic disease-modifying antirheumatic drugs in patients with rheumatoid arthritis after the use of at least one biologic disease-modifying antirheumatic drug: analyses from the pan-European TOCERRA register collaboration. Issue 9 (5th May 2018) - Lauper, Kim; Nordström, Dan C; Pavelka, Karel; Hernández, Maria Victoria; Kvien, Tore K; Kristianslund, Eirik Klami; Santos, Maria Jose; Rotar, Žiga; Iannone, Florenzo; Codreanu, Catalin; Lukina, Galina; Gale, Sara L; et al.
Abstract : Objective: To compare the effectiveness of tocilizumab (TCZ) and tumour necrosis factor (TNF) inhibitors (TNFi) as monotherapy or in combination with conventional synthetic disease-modifying antirheumatic drugs (DMARDs) in patients with rheumatoid arthritis (RA) after the use of at least one biologic DMARD (bDMARD). Methods: We included patients with RA having used at least one bDMARD from 10 European registries. We compared drug retention using Kaplan-Meier and Cox models and Clinical Disease Activity Index (CDAI) change over time with mixed-effects models for longitudinal data. The proportions of CDAI remission and low disease activity (LDA) at 1 year were compared using LUNDEX correction. Results: 771 patients on TCZ as monotherapy (TCZ mono), 1773 in combination therapy (TCZ combo), 1404 on TNFi as monotherapy (TNFi mono) and 4660 in combination therapy (TNFi combo) were retrieved. Crude median retention was higher for TCZ mono (2.31 years, 95% CI 2.07 to 2.61) and TCZ combo (1.98 years, 95% CI 1.83 to 2.11) than TNFi combo (1.37 years, 95% CI 1.30 to 1.45) and TNFi mono (1.31 years, 95% CI 1.18 to 1.47). In a country and year of treatment initiation-stratified, covariate-adjusted analysis, hazards of discontinuation were significantly lower among patients on TCZ mono or combo compared with patients on TNFi mono or combo, and TNFi combo compared with TNFi mono, but similar between TCZ mono and combo. Average adjusted CDAI change was similar between groups. CDAI remission and LDA rates were comparable between groups. Conclusion: With significantly longer drug retention and similar efficacy to TNFi combo, TCZ mono or combo are reasonable therapeutic options in patients with inadequate response to at least one bDMARD.